Seed mycoflora composition in sunflower - VISWANATHAN, R. (Indian Phytopathology, 2002)
In Oct. 1991 sunflower cv. Mordern and hybrid APSH-11 seeds were collected in Hyderabad, Andhra Pradesh, India. Fungal flora belonging to 13 genera were recorded with Alternaria, Fusarium, Macrophomina, Aspergillus, Cladosporium and Rhizopus being the predominant genera. This is the first report of 12 Alternaria spp., 5 Fusarium spp. and 4 Drechslera spp. on seed and kernel. Other species identified are listed.